Praktik Jurnalisme Lingkungan dalam Mitigasi Bencana Banjir Bandang di Masamba Kabupaten Luwu Utara - Ananda, Wahyu; Suhartina, Suhartina (IAIN Parepare, 2024)
This research aims to analyze the flood disaster mitigation process in Masamba, South Sulawesi, and evaluate the practice of environmental journalism in reporting on disaster mitigation efforts. The study employs a field research approach with a qualitative method. Data collection involves direct observation, interviews with relevant stakeholders, and content analysis of media coverage of the Masamba flood disaster. Data analysis techniques include data comprehension, data reduction, and conclusion. Findings indicate that the disaster mitigation process in Masamba initially progressed slowly due to the large-scale and recurrent nature of the events. At the same time, environmental journalism practices by mass media outlets still need to incorporate all aspects of environmental issues in their coverage. Additionally, the analysis reveals propaganda techniques utilized by the government to disseminate environmental recovery programs in Masamba. Research recommendations include enhancing government responsiveness in disaster mitigation, improving the integrity of mass media coverage related to environmental issues, and reviewing the government's propaganda techniques.